Raden Toemoenggoeng Endong Soeriapoetra Sebagai Bupati Bandung - Kharista Setyo Nur Utami; Wawan Darmawan (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2019)
The local historical event that occurred in Bandung Regency under R. E. Soeriapoetra during the revolution era was in a state of a refugee. This was due to attacks carried out by the Dutch who wanted to return to control Indonesia. In general, this study wants to answer the question about “How was Raden Toemoenggoeng Endoeng Soeriapoetra administered of his government amid the political crisis post-independence?”. This research aimed to analyze the local government under R.T.E. Soeriapoetra in Bandung Regency. To discuss the study, the researcher conducted a study using historicalmethods that include heuristics, source criticism, interpretation and historiography. Based on the results it can be explained that even though the administration under R.T.E. Soeriapoetra’s leadership was unstable, the local government still ran due to good communication and cooperation between the leaders, subordinates and the people. The undertaken program was only related to the government’s situation at that time such as making roads, repairing roads and supplying food, clothing for the fighters and also the people because at that time the process of government is in a state of a refugee. So that in his leadership as Regent of Bandung not many programs were made. He also served as Regent of Bandung in a short time which is only two years, starting from 1945-1947, because caught by the Dutch. He was also offered to become regent again under Pasundan State but he refused. He chose to be detained rather thanhaving to cooperate with the Dutch.